PENCARIAN RUTE OPTIMAL WISATA MOJOKERTO DALAM KASUS TRAVELING SALESMAN PROBLEM MENGGUNAKAN ALGORITMA GENETIKA - Adi Surya Jinggo Pratama; Abdul Khamid; Yesy Diah Rosita (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
Mojokerto is divided into two, namely the city and district, although it is divided into two, Mojokerto has a tourist spot that can be visited by those who want to find tourist attractions in Mojokerto in search of good and historic tours. If someone wants to go to a tourist spot, they can choose a travel agency that visits several tourist sites in large numbers to try to get a fast time. The purpose of this research is to be able to choose a tourist route, the application can find a good route in finding optimal route that can be passed with the shortest path and get the optimal number of trips in searching for tourism in Mojokerto within what has been mutually agreed upon. In the search for the optimal route for Mojokerto tourism in the TSP case using a Genetic Algorithm by conducting trials to get 3 optimal routes, namely 11-7-15-5-8-11, 11-2-12-3-4-1-11 and 11-14 -9-13-6-10-11 with a total distance of 32.5366, 40.2135 and 53.7129 KM. This test was obtained for route recommendations in tourism in Mojokerto, namely 32.5366 with the 11-7-15-5-8-11 route.